A unified call to action from Australian nursing and midwifery leaders: ensuring that Black lives matter. Issue 4 (3rd July 2020) - Geia, L.; Baird, K.; Bail, K.; Barclay, L.; Bennett, J.; Best, O.; Birks, M.; Blackley, L.; Blackman, R.; Bonner, A.; Bryant AO, R.; Buzzacott, C.; et al.
Abstract : Nurses and midwives of Australia now is the time for change! As powerfully placed, Indigenous and non-Indigenous nursing and midwifery professionals, together we can ensure an effective and robust Indigenous curriculum in our nursing and midwifery schools of education. Today, Australia finds itself in a shifting tide of social change, where the voices for better and safer health care ring out loud. Voices for justice, equity and equality reverberate across our cities, our streets, homes, and institutions of learning. It is a call for new songlines of reform. The need to embed meaningful Indigenous health curricula is stronger now than it ever was for Australian nursing and midwifery. It is essential that nursing and midwifery leadership continue to build an authentic collaborative environment for Indigenous curriculum development. Bipartisan alliance is imperative for all academic staff to be confident in their teaching and learning experiences with Indigenous health syllabus. This paper is a call out. Now is the time for Indigenous and non-Indigenous nurses and midwives to make a stand together, for justice and equity in our teaching, learning, and practice. Together we will dismantle systems, policy, and practices in health that oppress. The Black Lives Matter movement provides us with a 'now window' of accepted dialogue to build a better, culturally safe Australian nursing and midwifery workforce, ensuring that Black Lives Matter in all aspects of health care.